Automated Analysis of Protein Expression and Gene Amplification within the Same Cells of Paraffin-Embedded Tumour Tissue - Timo Gaiser; Lissa Berroa-Garcia; Ralf Kemmerling; Aparajita Dutta; Thomas Ried; Kerstin Heselmeyer-Haddad (Analytical Cellular Pathology)
Background: The simultaneous detection of protein expression and gene copy number changes in patient samples, like paraffin-embedded tissue sections, is challenging since the procedures of immunohistochemistry (IHC) and Fluorescence in situ Hybridization (FISH) negatively influence each other which often results in suboptimal staining. Therefore, we developed a novel automated algorithm based on relocation which allows subsequent detection of protein content and gene copy number changes within the same cell.